Sazonalidade da dieta e hábitos alimentares do gavião-peneira (Elanus leucurus) em habitats agrícolas no sul do Brasil - Scheibler, Daniel Ricardo [UNESP] (2003)
I analyzed the seasonal diet and food habits of the White-tailed Kite (Elanus leucurus) in an agricultural area (29o35'S, 52o12'W) near Venâncio Aires, southern Brazil, from 1,134 pellets collected from December 1997 to November 2000. Small mammals were the main prey (95%), followed by birds (4.6%), and reptiles plus insects (0.4%). The diet of the White-tailed Kite clearly reflected the agricultural impact on its habitat. The exotic rodent Mus musculus was the principal prey (67.4%) and, secondarily, the native rodents Akodon paranaensis and Necromys lasiurus, the marsupial Monodelphis dimidiata, and birds. The rodent Cavia aperea was also important due to its biomass. Mus musculus was the prey more taken during all seasons, however, it showed an evident pattern of seasonal variation, with maximum and minimum consumption rates during the winter and summer, respectively. There was relatively little variation in the kites' diet between years. During the kite non-breeding season (fall-winter), M. musculus furnished most of the biomass ingested. However, during its breeding season (spring-summer), native small mammal prey also contributed significantly. The biomass ingested per pellet and size of small mammal prey taken increased during the kite breeding season. This occurred primarily because of the greater consumption of adult individuals of M. musculus, A. paranaensis, N. lasiurus and M. dimidiata during this period